2013
DOI: 10.1002/dev.21108
|View full text |Cite
|
Sign up to set email alerts
|

The Development of end‐ and beginning‐state comfort in a cup manipulation task

Abstract: End-state comfort (ESC) is the tendency to assume comfortable postures at the end of simple object manipulation rather than at the start; and therefore has been used to assess the behavioral effects of motor planning. Adult-like patterns have been observed at age 9. Observations can extend to joint-action, such that adults consider the beginning-state comfort (BSC) of another, without sacrificing ESC; however, trends in children have yet to be delineated. This study investigated the development of ESC and BSC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
31
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 38 publications
5
31
3
Order By: Relevance
“…In typically developing children, recent large-scale cross-sectional studies showed that this ability improves between the ages of 3 and 10 years (JongbloedPereboom, Nijhuis-van der Sanden, Saraber-Schiphorst, Crajé, & Steenbergen, 2013;Scharoun & Bryden, 2014), confirming earlier studies (e.g., Weigelt & Schack, 2010). In children with CP only small-scale cross-sectional studies have been conducted, with a varying age span.…”
supporting
confidence: 70%
“…In typically developing children, recent large-scale cross-sectional studies showed that this ability improves between the ages of 3 and 10 years (JongbloedPereboom, Nijhuis-van der Sanden, Saraber-Schiphorst, Crajé, & Steenbergen, 2013;Scharoun & Bryden, 2014), confirming earlier studies (e.g., Weigelt & Schack, 2010). In children with CP only small-scale cross-sectional studies have been conducted, with a varying age span.…”
supporting
confidence: 70%
“…The Autism Spectrum Quotient: Children’s Version (AQ-Child; Auyeung et al, 2008) was used to quantify autistic traits in children with ASD (see Table 1). The performance of children with ASD was compared to 14 age-, hand preference- and sex-matched typically-developing children who were randomly selected from a larger study that included 75 typically-developing children ages 5–11 (Scharoun and Bryden, 2014). Parents of typically-developing children were not asked to complete the AQ-Child.…”
Section: Methodsmentioning
confidence: 99%
“…Here, adults will typically re-orient an object to facilitate a comfortable grasp (i.e., beginning-state comfort) for a co-actor, while maintaining a comfortable initial grasp (i.e., end-state comfort) for themselves (Gonzalez et al, 2011; Ray and Welsh, 2011). Little research has been conducted to delineate trends in children (Scharoun and Bryden, 2014). In one study, Scharoun and Bryden (2014) observed to demonstrate adult-like patterns of beginning state comfort at the age of 7 in typically-developing children.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations